PERANCANGAN APLIKASI LAYANAN ADMINISTRASI PERNIKAHAN BERBASIS WEB - Nur Fadilah; Titi Sriwahyuni (Universitas Negeri Padang, 2019)
Marriage becoming as a complex ceremonial nowadays. It’s no longer about the ceremony itself, but a bride also had to prepare about non-technical activities, such as wedding administration. There’s three common issues in handling wedding administration, bride’s lack of knowledge about wedding administration, complicated procedure, and there’s no clarity about wedding administrative’s cost standard. These problems are worrying, because it makes bride spent more times and money than it should. This wedding administrative application, is about to solve all those problems. Using PHP and YII2 Advanced framework, this application designed into a web-based application that provides information about wedding administrative. Users will get known about the real procedure in handling wedding administration, so it will takes less time and money. There’s no need for bride to frequently coming to Religion’s Administrative Office (KUA), because this application can handle it.Keywords: Application, married, marriage administration wedding, yii2 framework.